Paper mills integrated gasification combined cycle process with high energy efficiency for cleaner production. (10th July 2017) - Man, Yi; Hong, Mengna; Li, Jigeng; Yang, Sheng; Qian, Yu; Liu, Huanbin
Abstract: The papermaking industry has developed rapidly in recent years in China. Papermaking is a high-energy-consuming process. Consequently, large-scale paper mills usually have cogeneration systems that supply both electricity and steam for the papermaking process. In China, almost all these cogeneration systems in paper mills are powered by coal combustion, which consumes a large amount of energy and emits large amounts of greenhouse gas. The Integrated Gasification Combined Cycle (IGCC) technology is regarded as a clean and efficient method of coal utilization. In this work, an IGCC process for application in paper mills was designed and modeled. An IGCC coupled with a cascade refrigeration process (CRP) was further proposed in order to reuse the waste heat from the dryer section and improve the energy efficiency of the papermaking process. A paper with a conventional cogeneration system, one with an IGCC cogeneration system, and one with an IGCC coupled with a CRP cogeneration system were analyzed and compared in terms of energy efficiency, capital investment, operational cost, and dynamic payback period. The results showed that the integration of IGCC technology allows paper mills to be more competitive than those featuring conventional cogeneration systems in terms of energy efficiency and operational cost. Highlights: A paper mill integrated IGCC process is proposed. Waste heat of the papermaking process is reused in IGCC. New process saves 22% coal consumption and the energy efficiency increases 17%. Techno-economic analysis is conducted for validating its applicability.